A Comparison between Uni- and Bilateral tDCS Effects on Functional Connectivity of the Human Motor Cortex - Sehm, Bernhard; Kipping, Judy A.; Schaefer, Alexander; Villringer, Arno; Ragert, Patrick (Frontiers in Human Neuroscience, 2013)
tDCS over the primary motor cortex (M1) has been shown to induce changes in motor performance and learning. Recent studies indicate that tDCS is capable of modulating widespread neural network properties within the brain. However the temporal evolution of online- and after- effects of tDCS on functional connectivity within and across the stimulated motor cortices (M1) still remain elusive. In the present study, two different tDCS setups were investigated: (i) unilateral M1 tDCS (anode over right M1, cathode over the contralateral supraorbital region) and (ii) bilateral M1 tDCS (anode over right M1, cathode over left M1). In a randomized single-blinded crossover design, 12 healthy subjects underwent resting-state functional magnetic resonance imaging at rest (rs-fMRI) before, during and after 20 min of either bi-, unilateral or sham M1 tDCS. Seed-based functional connectivity analysis (FC) was used to investigate tDCS-induced changes across and within M1. We found that bilateral M1 tDCS induced (a) a decrease in interhemispheric FC during stimulation and (b) an increase in intracortical FC within right M1 after termination of the intervention. While unilateral M1 tDCS also resulted in similar effects during stimulation, no such changes could be observed after termination of tDCS. Our results provide evidence that depending on the electrode montage, tDCS acts upon a modulation of either intracortical and/or interhemispheric processing of M1.